Chad : Financial Sector Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2011)
The financial stability of Chad is analyzed in this study. Chad's financial system is one of the least developed in the CEMAC region. Chad's financial system is highly dependent on oil and agriculture, since it is a low-income country. In structuring the financial sector, the soundness and performance, short-term vulnerabilities, and supervision and crisis management of the Chadian banking system have been discussed with an emphasis on insurance and pension plans. In this study, the important role of legal and judicial environment in accessing the financial system is also explained.